MERANCANG STRATEGI DIGITALISASI UMKM DESA: PENDEKATAN PARTISIPATIF DI DESA TERIK, SIDOARJO - Enny Istanti; Indi Nuroini; R.M. Bramastyo Kusumo Negoro (LPPM Universitas Bhayangkara Surabaya, 2025)
The digital transformation of village MSMEs is an important agenda in encouraging economic equity and strengthening local independence. This article aims to design a participatory-based MSME digitization strategy in Terik Village, Krian, Sidoarjo, by exploring the needs, obstacles, and potential of local business actors. This study uses a descriptive qualitative approach with phenomenological methods, data collection techniques in the form of in-depth interviews, participatory observations, and Focus Group Discussions (FGD). The results of the study show that low digital literacy and lack of access to training are the main obstacles, but the active involvement of MSME actors in strategic planning increases their motivation and readiness to adopt technology. These findings contribute to the theory of community empowerment and technology acceptance and offer contextual and sustainable models of intervention. This study recommends the application of a participatory approach in the digital empowerment program of village MSMEs as well as the development of follow-up studies to enrich understanding of the phenomenon of community-based digital transformation